Buparlisib plus fulvestrant versus placebo plus fulvestrant for postmenopausal, hormone receptor-positive, human epidermal growth factor receptor 2-negative, advanced breast cancer: Overall survival results from BELLE-2. (November 2018) - Campone, Mario; Im, Seock-Ah; Iwata, Hiroji; Clemons, Mark; Ito, Yoshinori; Awada, Ahmad; Chia, Stephen; Jagiełło-Gruszfeld, Agnieszka; Pistilli, Barbara; Tseng, Ling-Ming; Hurvitz, Sara; Masuda, Norikazu; et al.
Abstract: Background: Buparlisib, a pan-phosphatidylinositol 3-kinase (PI3K) inhibitor, plus fulvestrant in the BELLE-2 study significantly improved progression-free survival (PFS) in patients with hormone receptor-positive, human epidermal growth factor receptor 2-negative advanced breast cancer. Patients and methods: In this phase III study, patients were randomised 1:1 to buparlisib (100 mg/day; continuously in 28-day cycles) or placebo, plus fulvestrant (500 mg on cycle 1 day 15, and day 1 of subsequent cycles). Overall survival (OS) was assessed in the overall population and patients with known PI3K pathway status (both had shown significant PFS improvements). OS by PIK3CA status in circulating tumour DNA (ctDNA) was an exploratory end-point. Results: A total of 2025 patients were screened for eligibility between 7th September 2012 and 10th September 2014, and 1178 received fulvestrant (500 mg) during a run-in phase; 31 discontinued. Of 1147 patients (median age 62 years), 98% had the Eastern Cooperative Oncology Group performance status ≤1, and 59% had visceral disease. Median follow-up from randomisation to data cut-off (23rd December 2016) was 37.6 months. Median OS trended in favour of the buparlisib arm in the overall population (33.2 versus 30.4 months; P = 0.045) and among patients with known PI3K pathway status (30.9 versus 28.9 months; P = 0.144); neither outcome was statistically significant. Median OS also trended in favour of buparlisib among patients with PIK3CA -mutant ctDNA (26.0 versus 24.8 months). Grade III/IV adverse events with ≥10% difference between the buparlisib versus placebo arms were elevated alanine aminotransferase (26% versus 1%), elevated aspartate aminotransferase (18% versus 3%) and hyperglycemia (15% versus <1%). Conclusions: OS results were in favour of buparlisib plus fulvestrant versus placebo plus fulvestrant; however, there is no statistical significance and more frequent grade III/IV adverse events were reported. Use of more selective PI3K inhibitors might provide the greatest clinical benefit and tolerable safety profile in this setting. Further evaluation of the predictive benefit of PIK3CA -mutant ctDNA is warranted. Trial registration number: NCT01610284 . Highlights: In this phase III study, median overall survival trended in favour of buparlisib plus fulvestrant versus placebo plus fulvestrant. ○ In the overall population (1147 patients), median OS was 33.2 versus 30.4 months; 1-sided P = 0.045. ○ In patients with known PI3K pathway status (851 patients), median OS was 30.9 versus 28.9 months; 1-sided P = 0.144. Both outcomes were not statistically significant and more frequent grade III/IV adverse events were reported. Investigation of selective PI3K inhibitors is warranted.